EFEKTIVITAS APLIKASI PHET DISERTAI LKS MATERI GERAK DAN GAYA UNTUK PEMBELAJARAN IPA DI SMP - Amala, Inggrid; Indrawati, Indrawati; Wicaksono, Iwan (EduFisika: Jurnal Pendidikan Fisika, 2020)
This study aims to describe the effectiveness of the PhET application which is equipped with worksheets about motion and force for science learning in junior high schools. This type of research is descriptive which is conducted on 8th grade junior high school students in one of junior high school in Lumajang Regency. The effectiveness of learning is shown from learning activities and increasing students’achievement. Data were collected by observation and test techniques. Learning activity data were analyzed descriptively using percentages and increasing students’ achievement were analyzed with normalized gain (Ng). One group pre-test and post-plan design are used in the data collection process. The results showed that the average student learning activity for four activity indicators (visual, mental, motor, and emotional) was 79,94% included in the good category and the average increase in learning outcomes was 0.67 (medium category). The conclusion of this study is the learning of science of motion and force in junior high school by using the PhET application is quite effective in improving student learning outcomes and the average student learning activity become good.